Views on Generation Islamic Banking Literacy: Bridging The Economic Gap and Improving Welfare - Nurkhasanah, Tri; Adinugraha, Hendri Hermawan; Shultoni, M. (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2024)
This research examines financial literacy, specifically related to Islamic banking, and its impact on Islamic banking lending and penetration in Indonesia. Qualitative and exploratory methods were used with data from a literature review and content analysis and FGDs. The results showed a majority understanding of Islamic banking, but variations in product usage among Generation Z. Islamic banking literacy is considered key to economic sustainability and alleviating generation Z poverty, emphasizing the importance of socializing this literacy to increase its effectiveness.Keywords: Financial Literacy, Islamic Banking, Generation Z This research examines financial literacy, specifically related to Islamic banking, and its impact on Islamic banking lending and penetration in Indonesia. Qualitative and exploratory methods were used with data from a literature review and content analysis and FGDs. The results showed a majority understanding of Islamic banking, but variations in product usage among Generation Z. Islamic banking literacy is considered key to economic sustainability and alleviating generation Z poverty, emphasizing the importance of socializing this literacy to increase its effectiveness.